Implant Prosthetic Rehabilitation with Bone Regenerative Techniques after Fracture of the Upper Central Incisors. (12th May 2013) - Amato, Massimo; Bruno, Vincenzo; Pantaleo, Giuseppe; Cerutti, Antonio; Spagnuolo, Gianrico; Sammartino, Gilberto
Abstract : A case of implant-bone prosthetic rehabilitation, after the fracture of the maxillary central incisors, which had been treated with grafting of a bone substitute, is reported. This case was followed by the normal procedures of implantology within the traditional timeframe for bone regeneration. However, a barrier membrane was not used which shows that even along with the use of graft material a sufficient amount of bone could be achieved for a subsequent rehabilitation. Therefore, after a five-year follow-up period, osseointegration was maintained with no marginal bone loss.